Improved Environmental Management Performance in the Crude Palm Oil (CPO) Production Process using a Life Cycle Assessment Approach - Mutiara Putri Ayu; Rizki Aziz; Taufiq Ihsan (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2026)
The palm oil production process at XYZ company, from the plantation subsystem, such as maintenance and harvesting, to processing in the mill, has the potential for significant environmental impacts, including greenhouse gas emissions from the use of diesel fuel. This study aims to evaluate the potential environmental impacts of producing one ton of Crude Palm Oil (CPO) at XYZ company using a Life Cycle Assessment (LCA) with a cradle-to-gate approach. The CML-IA Baseline method was employed, focusing on three main impact categories: Global Warming Potential (GWP 100a), Acidification Potential (AP), and Eutrophication Potential (EP). Primary data were collected directly from XYZ company through interviews, observations, and documentation, supported by relevant secondary data. Life Cycle Inventory (LCI) analysis quantified inputs such as fertilizers, diesel fuel, and electricity, as well as outputs in the form of liquid and solid waste. The Life Cycle Impact Assessment (LCIA) results indicate that factory processing operations are the primary contributors to environmental impacts. The GWP 100a impact value was identified as 2×10? kg CO? eq./ton CPO, the AP value as 18.5 kg SO? eq./ton CPO, and the EP value as 7.8 kg PO? eq./ton CPO, with the most significant contributions coming from diesel fuel consumption and electricity use in the loading ramp process. Improvement recommendations focus on optimizing the replacement of diesel fuel with biodiesel to minimize the impact.